2006
DOI: 10.1111/j.1475-4959.2006.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Good, bad or ‘necessary evil’? Reinterpreting the colonial burning experiments in the savanna landscapes of West Africa

Abstract: A simple ecological model underlies contemporary fire policy in many West African countries. The model holds that the timing (or seasonality) of annual savanna fires is a principal determinant of vegetation cover. The model's origin can be traced to the ideas held by influential colonial scientists who viewed anthropogenic fire as a prime force of regional environmental degradation. The main evidence in support of the model derives from the results of a series of long‐term burning experiments carried out durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 54 publications
(70 reference statements)
4
125
0
2
Order By: Relevance
“…Burrows et al (1979) suggested that in reality for police to be effective, they need the support of the community, because for the police make any arrest, they will do so using information obtained from the public rather than catching the offender red-handed. Policing normally target to punish illegitimate use of fires, minimise errors and negligence as preventive measures (Laris and Wardell 2006). However, this has an effect of isolating the society by treating them as agents that causes wildland fires, than those that can prevent.…”
Section: Increasing Enforcement Of Regulationsmentioning
confidence: 99%
“…Burrows et al (1979) suggested that in reality for police to be effective, they need the support of the community, because for the police make any arrest, they will do so using information obtained from the public rather than catching the offender red-handed. Policing normally target to punish illegitimate use of fires, minimise errors and negligence as preventive measures (Laris and Wardell 2006). However, this has an effect of isolating the society by treating them as agents that causes wildland fires, than those that can prevent.…”
Section: Increasing Enforcement Of Regulationsmentioning
confidence: 99%
“…For example, in some areas burning begins very early in the dry season and produces a fine-scale mosaic over time, while in others burning begins later and produces a pattern of later, larger and more contiguous fires (see Figure 5) [23]. Mali has experienced several shifts in fire policy over the past few decades [33,35] as well as a major and prolonged drought making it ideal for a case study.…”
Section: Case Study Of Malian Savanna Fire Regimesmentioning
confidence: 99%
“…Anti-fire policy has a long history in the region [35,43]. During the mid-1980s, a universal ban on burning was implemented in Mali that made all savanna fires illegal.…”
Section: Fire Policymentioning
confidence: 99%
“…The hunting governance as practiced today is a product of this history, being influenced by both the precolonial customary governance and the changes that the hunting systems have undergone since colonial rule and independence. Similarly drastic governance changes in response to colonial rule have been documented in other parts of Africa (Laris and Wardell 2006), where many of the past systems were present only a few decades ago, and much of the traditional practices have been further eroded in the face of market forces and modern practices (Marks 1979, Forbes et al 2014). …”
Section: Discussionmentioning
confidence: 64%